Efficacy and Safety of Labetalol Versus Methyldopa for Blood Pressure Control in Pregnant Women With Hypertension: Efficacy and Safety of Labetalol Versus Methyldopa for Blood Pressure Control in Pregnant Women With Hypertension - Yahya, Nur Khalisha (JURNAL ILMIAH DHDT - KEBIDANAN, 2026)
Hypertension in pregnancy is a major contributor to maternal morbidity and mortality worldwide. Labetalol and methyldopa are widely recommended as first-line antihypertensive therapy; however, uncertainty remains regarding comparative effectiveness for optimal blood pressure (BP) control. This Evidence-based case Report evaluates the efficacy and safety of these agents to inform therapeutic selection. A comprehensive literature search was conducted in PubMed, Cochrane Library, Google Scholar, and EBSCO using the keywords (“Hypertension” AND “Pregnancy” AND “Labetalol” AND “Methyldopa” AND “Blood Pressure Control”). Eligible studies included randomized controlled trials (RCTs) and systematic reviews/meta-analyses comparing labetalol and methyldopa in pregnant women with hypertension were included. Data extraction prioritized maternal BP outcomes, reporting effect sizes as relative risk (RR), absolute risk reduction (ARR), and number needed to treat (NNT) with 95% confidence intervals (CI). Quality assessment was performed using the Centre for Evidence-Based Medicine (CEBM) appraisal tool. From 355 studies screened, two RCTs met eligibility. Labetalol provided a faster reduction in blood pressure (RR 1.35; 95% CI 1.01–1.80; NNT ≈ 6), while overall blood pressure control was comparable to methyldopa in longer-term outcomes (RR 0.99; 95% CI 0.92–1.06).Both labetalol and methyldopa demonstrate comparable clinical effectiveness as first-line therapy for hypertension in pregnancy. Drug selection should be individualized based on clinical urgency, tolerance, availability, and monitoring capacity. Early treatment and close follow-up remain the primary determinants of maternal–fetal outcomes